2010
DOI: 10.1038/oby.2010.63
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Obesity, Flow Rate of Whole Saliva, and Dental Caries in Adolescents

Abstract: In a cross‐sectional study design, we test the hypothesis whether childhood obesity is associated with reduced flow rate of stimulated whole saliva and dental caries. Obese adolescents (n = 65) with a mean age of 14.5 years and normal weight subjects (n = 65) with a mean age of 14.2 years were clinically examined with respect to dental caries, visible plaque accumulation (visible plaque index (VPI%)), gingival inflammation in terms of bleeding on probing (BOP%) as well as answered a questionnaire concerning me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
120
1
25

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(163 citation statements)
references
References 30 publications
(40 reference statements)
13
120
1
25
Order By: Relevance
“…Other studies could not find any association between body weight and prevalence of caries 18,19 either, which agrees with our findings. On the other hand, other findings showed that obese individuals had more carious surfaces than those with normal weight 20 .…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Other studies could not find any association between body weight and prevalence of caries 18,19 either, which agrees with our findings. On the other hand, other findings showed that obese individuals had more carious surfaces than those with normal weight 20 .…”
Section: Discussionmentioning
confidence: 66%
“…On the other hand, other findings verified a positive association between gingival inflammation and obesity in children and adolescents 20,25 . The study by Franchini et al 25 also showed a significant effect of obesity on children and adolescents, aged 10 to 17, and stressed that this association may be the result of a combination of metabolic inflammation and poor oral hygiene.…”
Section: Discussionmentioning
confidence: 76%
“…5,[8][9][10]15,19,[22][23][24]27,29,33,36,40,41 Eight studies included adjustments for age and sex, 6,19,23,27,29,33,36,41 two only for sex, 15,22 and fi ve for consumption of any type of food, such as soft drinks, 10,24 fruits or snacks between meals, 10 "fast food", 10 and milk, 9 as well as daily sugar consumption 19 and "snack" consumption more than three times a day. 29 Among the 28 articles, 13 were considered to have good scientifi c evidence according to the criteria of Downs & Black.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, most research has focused on parameters such as flow rate, electrolytes, and total protein amounts, mainly in the context of the development of dental caries (e.g. [28]). The aims of this study were to identify putative changes in salivary protein profiles in morbidly obese women and to evaluate the effect of weight loss on these profiles.…”
Section: Introductionmentioning
confidence: 99%